A COMPARATIVE STUDY OF RED DRAGON FRUIT JUICE WITH RED GUAVA JUICE ON HEMOGLOBIN LEVELS IN ADOLESCENTS - Damayanti, Santi; Lestiawati, Endang; Anggreni, Ni Wayan Diah Novi (Universitas Respati Yogyakarta, 2021)
Anemia causes learning achievement to decrease. Hematopoiesis requires macronutrients ound in red dragon fruit and red guava. Objective of research to determine differences in the effectiveness of administration of red guava juice and red dragon fruit juice on hemoglobin (Hb) levels in young women. This type of research is quasi-experimental research design with pre-test and post-test without control. The sampling technique uses probability sampling. Data analysis using Paired T-Test and Independent T-Test. The mean Hb level of red guava juice group was pre test 13.18 gr / dL and post test 14.71 gr / dL with P value 0.000. The mean Hb levels of the red dragon fruit juice group were 13.13 gr / dL pre test and 15.41 gr / dL post test with. P Value 0,000. Red guava juice and red dragon fruit juice were equally effective in increasing Hb levels.